Cardiovascular risk factors and their association with carotid intima media thickness in children in Western India - Jain, Ashish Kumar; Dani, Sameer; Jain, Parul (International Journal of Research in Medical Sciences, 2018)
Background: Cardiovascular disease occurs in early in Indians risk factors of which may start from childhood. Objective was to identify CV risk factors in children and study their association with carotid intima media thickness. Methods: In this cross-sectional study, we studied children aged 4 to 14 years visiting our institute for routine health check-up. Data was collected on demographics, clinical and biochemical parameters. All patient underwent electrocardiographic, 2-D echocardiography examination. Carotid intima media thickness (CMT) was observed by carotid ultrasound. Results: In 378 children enrolled in the study, mean age was 9.1±2.6 years with 74.6% being males. Mean body mass index was 18.7±3.9 kg/m2. Among various CV risk factors, dyslipidemia (46.6%) was most common followed by family history of premature CV disease (9.5%), hypertension (4.49%), obesity (3.17%), smoking (1.05%). High dietary fat intake was seen in 22.2% cases. CMT showed significant association with age (p=0.027), BMI (p=0.031), systolic (p=0.026) and diastolic (p=0.036) blood pressure, high-density lipoprotein cholesterol levels (p=0.001), and low-density lipoprotein cholesterol (p=0.047). No association with fat intake or total calorie intake was observed. Conclusions: Dyslipidemia along other risk factors can be present as CV risk factor from early childhood. Screening of children for such risk factors to mitigate the risk of atherosclerotic CV disease in adulthood.